Perception and practice towards alcohol consumption among a government boy’s pre-university college students-a cross sectional study - Basagoudar, Shashidhar S.; R., Chandrashekhar; Hatanoor, Shivappa; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2017)
Background: Harmful use of alcohol consumption can lead to various health hazards and pre-university students are vulnerable for abuse of substances like alcohol. Hence this study was aimed to find out the prevalence and perception towards alcohol consumption among students of government boy’s college and to find out some factors affecting alcohol consumption among students. Methods: A cross sectional study conducted among purposively selected students of government pre-university (PU) college for boys. Data was collected through pre-structured questionnaire. Alcohol consumption was assessed by self-reporting through questionnaire. Results: In the present study 7% students have consumed alcohol at least once in their life time. Mean age of initiation of alcohol consumption was 14.89 years. 23.7% of students said that alcohol consumption can lead to cancer and 13.3% students knew it leads to liver damage, 18.1% felt it leads to heart problems. Among the current alcohol consumers 41.7% said they have driven the vehicle under influence of alcohol. Among the current alcohol consumers 75% have thought to quit the alcohol consumption at least once. Having family history of alcohol consumption was significantly associated with alcohol consumption among students. Conclusions: Alcohol consumption is prevalent in the pre-university college students and family history is a major risk factor for the alcohol consumption. Many alcohol consumers have driven the vehicle under the alcohol consumption in spite of the legal prohibition. Parental and peer involvement is crucial in reducing the prevalence of alcohol consumption among PU students.